2010
DOI: 10.1007/s11665-009-9590-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxidation and SiO2 Coating on the Bonding Strength of Ti-Porcelain

Abstract: Investigations on the effect of oxidation on titanium-ceramic adhesion were performed. Cast pure titanium was subjected to surface modification by preoxidation and introduction of an intermediate layer of SiO 2 by sol-gel process. Specimens were characterized by TG-DSC, XRD, and SEM/EDS. The adhesion between the titanium and porcelain was evaluated by three-point flexure bond test. Failure of the titanium-porcelain with preoxidation treatment predominantly occurred at the titanium-oxide interface. Preoxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Our EDS analysis results indicated that no contamination by the Al 2 O 3 particles was present on the sandblasted Ti surface (SB group), which also demonstrated sufficient bonding with the porcelain (bond strength 28.76 MPa). This bond strength value was similar to previously reported values …”
Section: Discussionsupporting
confidence: 93%
“…Our EDS analysis results indicated that no contamination by the Al 2 O 3 particles was present on the sandblasted Ti surface (SB group), which also demonstrated sufficient bonding with the porcelain (bond strength 28.76 MPa). This bond strength value was similar to previously reported values …”
Section: Discussionsupporting
confidence: 93%
“…The effect of cooling rate is due to the change of heat stress of Ti-ceramic interface. 30 As a conclusion, the bond of ceramic over titanium is a sensitive technique influenced by the effects provoked mainly by the layer of surface oxide. Titanium and titanium alloys, based on their physical and chemical properties suitable for titanium-ceramic restorations, but careful selection of processing methods, ceramic materials, laboratory skill and strict protocol for ceramic bonding to titanium are necessary to improve the bonding between titanium and ceramic.…”
Section: Discussionmentioning
confidence: 98%
“…26 The use of Au (gold), 6,29 Si 3 N 4 , chrome, SiO 2 and TiO 2 as intermediate layers has been investigated. 30 Several study showed that the titanium ceramic adhesion could be improved by coating cast titanium surface with Au. 29 This can be explained by the formation a Ti-Au intermetallic compound and surpressed the formation of a Ti-deficient intermediate layer, resulting in improved adherence between ceramic and titanium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bond strength primarily depends on the mechanical and chemical properties of the interface between the metal and porcelain 9,10) . Although extensive studies have employed different surface treatments of Ti prior to porcelain sintering [11][12][13][14][15][16][17][18][19] , a simple and practical technique to improve Ti-porcelain bond strength has not been well determined, and the underlying mechanism for the bonding of Ti and porcelain is not well understood.Chemical solution treatment is a method that can be used to treat and clean metallic surfaces for clinical applications 20) . In industrial fields, an alkaline or acid solution has been successfully employed to clear superficial pollutants from Ti and Ti alloys 21) .…”
mentioning
confidence: 99%